The Impact of Social Media on Qur’anic Studies in Northern Nigeria: An Assessment of its Challenges and Opportunities - Rabiu, Aliyu Alhaji; Usman El-Nafaty, Nabeela; Abubakar Shariff, Ikilima; Dahiru Idriss, Ibrahim (Jurnal Usuluddin, 2024)
The increasing prevalence of social media among students and teachers in Islamiyyah schools in Northern Nigeria has raised significant concerns about its impact on Qur’anic education. These platforms, while offering innovative opportunities for engagement and learning, also introduce challenges such as distractions, time mismanagement, and exposure to unethical content. This duality necessitates urgent exploration to understand how social media influences Qur’anic memorization, recitation, and teaching practices. This study employs a mixed-method approach, combining thematic analysis of qualitative interviews and descriptive statistical analysis of survey data collected from 141 respondents. Key findings reveal that while social media facilitates global connectivity and flexible learning methods, it simultaneously detracts from the focus required for effective Qur’anic education. The study emphasizes the importance of structured guidance and regulation to balance the opportunities and challenges presented by social media. Recommendations include integrating tailored digital tools, enhancing parental and institutional oversight, and promoting mentorship to optimize the use of social media in Qur’anic studies.